Intensity of anxiety is modified via complex integrative stress circuitries - Smith, Justin P. (Psychoneuroendocrinology, 2015)
Escalation of anxious behavior while environmentally and socially relevant contextual events amplify the intensity of emotional response produces a testable gradient of anxiety shaped by integrative circuitries. Apprehension of the Stress-Alternatives Model apparatus (SAM) oval open field (OF) is measured by the active latency to escape, and is delayed by unfamiliarity with the passageway. Familiar OF escape is the least anxious behavior along the continuum, which can be reduced by anxiolytics such as icv neuropeptide S (NPS). Social aggression increases anxiousness in the SAM, reducing the number of mice willing to escape by 50%. The apprehension accompanying escape during social aggression is diminished by anxiolytics, such as exercise and corticotropin releasing-factor receptor 1 (CRF(1)) antagonism, but exacerbated by anxiogenic treatment, like antagonism of α(2)-adrenoreceptors. What is more, the anxiolytic CRF(1) and anxiogenic α(2)-adrenoreceptor antagonists also modify behavioral phenotypes, with CRF(1) antagonism allowing escape by previously submissive animals, and α(2)-adrenoreceptor antagonism hindering escape in mice that previously engaged in it. Gene expression of NPS and brain-derived neurotrophic factor (BDNF) in the central amygdala (CeA), as well as corticosterone secretion, increased concomitantly with the escalating anxious content of the mouse-specific anxiety continuum. The general trend of CeA NPS and BDNF expression suggested that NPS production was promoted by increasing anxiousness, and that BDNF synthesis was associated with learning about ever-more anxious conditions. The intensity gradient for anxious behavior resulting from varying contextual conditions may yield an improved conceptualization of the complexity of mechanisms producing the natural continuum of human anxious conditions, and potential therapies that arise therefrom.